2004
DOI: 10.1073/pnas.0307149101
|View full text |Cite
|
Sign up to set email alerts
|

Paired-pulse depression of unitary quantal amplitude at single hippocampal synapses

Abstract: At central synapses, quantal size is generally regarded as fluctuating around a fixed mean with little change during short-term synaptic plasticity. We evoked quantal release by brief electric stimulation at single synapses visualized with FM 1-43 dye in hippocampal cultures. The majority of quantal events evoked at single synapses were monovesicular, based on examination of amplitude distribution of ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid-receptor-mediated responses. Consistent with previous find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 38 publications
8
77
1
Order By: Relevance
“…It is generally agreed that an increase in the P r occurs during facilitation; however, it is still debated whether the increase in P r is solely responsible for the facilitation or whether postsynaptic modifications also take place. Several studies reported an exclusive presynaptic alteration (Gulyas et al, 1993;Stevens and Wang, 1995;Dobrunz and Stevens, 1997;Hanse and Gustafsson, 2001;Silver et al, 2003;Chen et al, 2004;Lawrence et al, 2004), but evidence has also been published supporting significant postsynaptic modifications, including an increased quantal size after multivesicular release (Oertner et al, 2002;Conti and Lisman, 2003) or removing the polyamine block from certain postsynaptic glutamate receptors (Rozov and Burnashev, 1999). To some extent, the reason for the discrepancy is likely attributable to differences in experimental approaches, such as the preparations, the age of the animals, and the identity of the synapses examined.…”
Section: Discussionmentioning
confidence: 82%
“…It is generally agreed that an increase in the P r occurs during facilitation; however, it is still debated whether the increase in P r is solely responsible for the facilitation or whether postsynaptic modifications also take place. Several studies reported an exclusive presynaptic alteration (Gulyas et al, 1993;Stevens and Wang, 1995;Dobrunz and Stevens, 1997;Hanse and Gustafsson, 2001;Silver et al, 2003;Chen et al, 2004;Lawrence et al, 2004), but evidence has also been published supporting significant postsynaptic modifications, including an increased quantal size after multivesicular release (Oertner et al, 2002;Conti and Lisman, 2003) or removing the polyamine block from certain postsynaptic glutamate receptors (Rozov and Burnashev, 1999). To some extent, the reason for the discrepancy is likely attributable to differences in experimental approaches, such as the preparations, the age of the animals, and the identity of the synapses examined.…”
Section: Discussionmentioning
confidence: 82%
“…Variance analysis also showed that quantal amplitudes stayed constant during a high-frequency train. It is interesting to note that shortterm synaptic depression accompanies decrease in quantal sizes, which is not attributable to postsynaptic mechanisms at hippocampal synapses (Chen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…13,16,18 In brief, the hippocampal CA1-CA3 region was dissected out and incubated for 30 min in 0.05% trypsin-EDTA solution (pH 7.2). After enzyme treatment, tissue blocks were gently triturated with a fire-polished Pasteur pipette.…”
Section: Cell Culturementioning
confidence: 99%
“…For example, microisland cultures containing only a single autaptic neuron or a few neurons have been widely used to study molecular and cellular mechanisms of synaptic transmission and synaptic plasticity. [12][13][14][15][16][17][18] With the usually low efficiency of 1-5%, Ca 2+ -phosphate transfection is not suitable for transfecting single autaptic neurons to study gene functions. In order to transfect single autaptic neurons in microisland cultures, the transfection efficiency has to be greatly improved.…”
Section: Introductionmentioning
confidence: 99%